Genetic marker: a genome mapping tool to decode genetic diversity of livestock animals - Panchariya, Darshan C.; Dutta, Priyanka; Ananya,; Mishra, Adyasha; Chawade, Aakash; Nayee, Nilesh; Azam, Sarwar; Gandham, Ravi Kumar; Majumdar, Subeer; Kushwaha, Sandeep Kumar (Frontiers in Genetics, 2024)
Genotyping is the process of determining the genetic makeup of an organism by examining its DNA sequences using various genetic markers. It has been widely used in various fields, such as agriculture, biomedical and conservation research, to study genetic diversity, inheritance, the genetic basis of disease-associated traits, evolution, adaptation, etc. Genotyping markers have evolved immensely and are broadly classified as random markers( RFLP, RAPD, AFLP, etc.) and functional markers(SCoT, CDDP, SRAP, etc.). However, functional markers are very limited in genotype studies, especially in animal science, despite their advantages in overcoming the limitations of random markers, which are directly linked with phenotypic traits, high specificity, and similar logistic requirements. The current review surveyed the available random and functional markers for genotyping applications, focusing on livestock including plant and microbe domains. This review article summarises the application, advantages, and limitations of developed markers and methods for genotyping applications. This review aims to make the reader aware of all available markers, their design principles, and methods, and we discuss the marker inheritance patterns of RLFP and AFLP. The review further outlines the marker selection for particular applications and endorses the application of functional markers in genotyping research.1. The genotyping techniques enable us to explore the wealth of information encoded within the genome. 2. Various DNA markers have been developed. However, only some DNA markers are widely used in human, animal, and plant research due to their theoretical and technical advantages and capacity for sample processing and analysis. 3. This review provides an overview of all known markers and methods for genotyping studies. It summarises their potential for application, advantages, limitations, and inheritance patterns to choose markers for genotyping applications. 4. Various functional markers have been developed and widely used in plant science. However, it is underutilised in animal science despite several advantages over random markers.